2002
DOI: 10.1182/blood-2002-04-1121
|View full text |Cite
|
Sign up to set email alerts
|

Human myeloma cells stimulate the receptor activator of nuclear factor-κB ligand (RANKL) in T lymphocytes: a potential role in multiple myeloma bone disease

Abstract: The biologic mechanisms involved in the pathogenesis of multiple myeloma (MM) bone disease are not completely understood. Recent evidence suggests that T cells may regulate bone resorption through the cross-talk between the critical osteoclastogenetic factor, receptor activator of nuclear factor-B ligand (RANKL), and interferon ␥ (IFN-␥) that strongly suppresses osteoclastogenesis. Using a coculture transwell system we found that human myeloma cell lines (HMCLs) increased the expression and secretion of RANKL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
184
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(194 citation statements)
references
References 41 publications
(42 reference statements)
6
184
0
4
Order By: Relevance
“…[41][42][43] Interestingly, our data suggest that other than angiogenic cytokines, HIF-1a suppression affects expression and production of MM-derived pro-osteoclastogenic factors that are known to be involved in osteoclast formation and bone destruction such as CCL3/MIP1a 44 and IL-7. 45 To the best of our knowledge, this is the first time that the capacity of HIF-1a has been reported to regulate pro-osteoclastogenic cytokine in MM cells, although the evidence that CCL3/MIP1a and IL-7 are potential target genes of HIF-1a has been shown in other cell types such as acute myeloid leukemia cells for CCL3/MIP1a 46 and mesenchymal/osteoblastic cells for IL-7. 47 To evaluate the role of HIF-1a as a potential target in MM we used two different in vivo models: the subcutaneously and the intratibial model.…”
Section: Discussionmentioning
confidence: 82%
“…[41][42][43] Interestingly, our data suggest that other than angiogenic cytokines, HIF-1a suppression affects expression and production of MM-derived pro-osteoclastogenic factors that are known to be involved in osteoclast formation and bone destruction such as CCL3/MIP1a 44 and IL-7. 45 To the best of our knowledge, this is the first time that the capacity of HIF-1a has been reported to regulate pro-osteoclastogenic cytokine in MM cells, although the evidence that CCL3/MIP1a and IL-7 are potential target genes of HIF-1a has been shown in other cell types such as acute myeloid leukemia cells for CCL3/MIP1a 46 and mesenchymal/osteoblastic cells for IL-7. 47 To evaluate the role of HIF-1a as a potential target in MM we used two different in vivo models: the subcutaneously and the intratibial model.…”
Section: Discussionmentioning
confidence: 82%
“…We deduce that the level of iNKT cells frequency and production function of IFN‐γ relate to the state of bone destruction, especially osteoclastogenesis. In addition, some studies concluded that immune cells such as T cells express RANKL, but T cells also resist osteoclastogenesis by producing interferon‐γ (IFN‐γ), which counterbalance the action of RANKL 4, 7, 8. iNKT cells acting as a special T cell may be involved in bone destruction, especially osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…As we all know, osteoclastogenesis and activation of bone resorption are regulated by the RANK/RANKL/OPG axis 3. Immune cells, such as T cells, express RANKL, which contributed to the pathogenesis of MBD 4, 5, 6. While T cells also resist osteoclastogenesis by producing interferon‐γ (IFN‐γ), which counterbalance the action of RANKL 4, 7, 8.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of RANKL and decreased OPG expression in myeloma are illustrated by the high levels of sRANKL and the low level of OPG measured by ELISA in the serum of patients with myeloma compared with their respective controls (Terpos et al, 2003). One interesting point to note is that induction of these responses was dependent on cell-to-cell contact, as another transwell system showed no effect on RANKL expression (Giuliani et al, 2002).…”
Section: Multiple Myeloma: a Disease Associated With A Fflgh Level Ofmentioning
confidence: 99%